Disorder by disorder and flat bands in the kagome transverse field Ising model - Powalski, M.; Coester, K.; Moessner, R.; Schmidt, Kai Phillip (Physical Review B, 2013)
We study the transverse field Ising model on a kagome and a triangular lattice using high-order series expansions about the high-field limit. For the triangular lattice our results confirm a second-order quantum phase transition in the 3d XY universality class. Our findings for the kagome lattice indicate a notable instance of a disorder by disorder scenario in two dimensions. The latter follows from a combined analysis of the elementary gap in the high- and low-field limit which is shown to stay finite for all fields h. Furthermore, the lowest one-particle dispersion for the kagome lattice is extremely flat acquiring a dispersion only from order 8 in the 1/h limit. This behavior can be traced back to the existence of local modes and their breakdown which is understood intuitively via the linked cluster expansion. DOI: 10.1103/PhysRevB.87.054404